A study of direct-sequence spread spectrum/delta modulation system - Lim, Rudy Alkuino (1988)
This study focuses on the design, construction, practical and theoretical performance evaluation of Direct-Sequence Spread Spectrum/ Delta Modulation System. The prototype model of the system is a Direct-Sequence Spread Spectrum system intended for digital communication over wire transmission channel using baseband modulation, speficifically Continously Variable Slope Delta Modulation at 16 kbps. The coding used was a maximal-length Gold Code and a test tone of 1 KHZ frequency was used as the input signal in order to determine the performance of the system. The Signal-to-Quantization Noise ratio of the CVSD (Continously Variable Slope Delta Modulator) used was determined both through mathematical calculations and test measurements. The BER of the system was determined theoretically and it is computed with pulse-noise jamming signal introduced in the transmission channel to demonstrate the advantage of spreading the bandwidth of data before transmission. The circuit design of the system was made to make use, as much as possible the available electronic components in the local markets, except for the Adaptive Delta Modulator/ Demodulator, used for general communications which had to be imported from Hongkong.
Typescript.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Spread spectrum communications; Digital communications